American, born Hungary Kertész, Capa, and the Hungarian American photographic legacy - Nyerges, Alexander Lee 1957-; Kincses, Károly 1954- (VMFA, Virginia Museum of Fine Arts, 2024)
"An expansive look at the significant role of Hungarian immigrants in shaping American photographic culture and practice in the twentieth century. This beautifully illustrated book explores the cultural conditions for photography in Hungary in the first half of the twentieth century and the exodus of groundbreaking Hungarian artists, many of whom journeyed to Berlin, Paris, or London before settling in the United States. The story of the bounty of intellectual and artistic talent that departed Hungary during this period is told in depth, from the photojournalistic legacy of the Capa brothers and Martin Munkácsi to the deeply experimental work made in the United States by artists such as László Moholy-Nagy and György Kepes to the portraits of cinema icons by André de Dienes, including Marilyn Monroe, which helped fuel Hollywood's Golden Age. The book also introduces the major but underrecognized talent of artists, including John Albok, Anna Barna, Ferenc Berko, Michael Simon, and Paula Wright. The publication's essays explore the complex legacy of more than thirty Hungarian-born photographers and reflect on their journeys to the US in the context of Hungarian emigration for more than a hundred and fifty years. By tracing the impact of these celebrated and unheralded photographers alike, American, Hungary Born underscores the significant role of Hungarian immigrants in shaping American photographic culture and practice in the twentieth century."
This catalogue accompanies the exhibition American, born Hungary: Kertész, Capa, and the Hungarian American photographic legacy, organized by the Virginia Museum of Fine Arts and presented at the Museum of Fine Arts, Budapest, April 4, 2024 - August 29, 2024, Virginia Museum of Fine Arts, October 5, 2024 - January 26, 2025, and the George Eastman Museum, September 26, 2025 - March 1, 2026
Artists include: Lucien Aigner, John Albok, Anna Barna, Ferenc Berko, Cornell Capa, Robert Capa, Helene Beck Deutch, Stephen Deutch, André de Dienes, Orshi Drozdik, Arnold Eagle, Jolán Gross-Bettelheim, Francis Haar, Nicholas Ház, Bela Kalman, György Kepes, André Kertész, László Kondor, Balthazar Korab, György Lőrinczy, László Moholy-Nagy, Martin Munkácsi, Nickolas Muray, Marion Palfi, Sylvia Plachy, Irma Biró and Imre Révész, Michael Simon, Cornel Somogy, Marcel Sternberger, Max Thorek, László Josef Willinger, Paula Wright, Ylla
Keywords: Geschichte 1900-2000; Fotograf; Magyaren; USA; Hungarian American photographers / Exhibitions; Photography / Hungary / History / 20th century / Exhibitions; Photography / America / History / 20th century / Exhibitions; Photojournalism / Hungary / History / 20th century / Exhibitions; Photojournalism / America / History / 20th century / Exhibitions; Photography, Artistic / Exhibitions; Bildband; Ausstellungskatalog -- Szépművészeti Múzeum -- Budapest; Ausstellungskatalog -- Virginia Museum of Fine Arts -- 05.10.2024-26.01.2025 -- Richmond, Va.; Ausstellungskatalog -- George Eastman Museum -- 26.09.2025-01.03.2026 -- Rochester, NY